Manajemen Media Sosial Sebagai Branding Dalam Pengelolaan Perpustakaan - Adzkiyah Mubarokah; Ida Susilawati (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2023)
This research is entitled "Management of Social Media as Branding in Library". This study uses field research methods with a qualitative approach. Where researchers conducted direct interviews with librarians who were at Grahatama Pustaka to ask questions related to what they wanted to study. The purpose of this study is to see how social media management builds Grahatama Pustaka branding. The results obtained in this study were Grahatama Pustaka applying the 7P marketing mix theory to build library branding through social media owned by Grahatama Pustaka. The mix includes product, price, place, people, promotion, process, and physical evidence.